2020
DOI: 10.1002/tea.21625
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the classroom science investigation

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
79
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 71 publications
(100 reference statements)
1
79
0
17
Order By: Relevance
“…As tendências inovadoras de ensino de ciências apontam as potencialidades do engajamento dos estudantes em práticas como argumentação, modelagem e explicação; e que tais práticas estão interligadas ao conhecimento conceitual de ciências. Porém, os modos de promover esta associação e suas implicações ainda não estão claros (Manz, Lehrer & Schauble, 2020).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…As tendências inovadoras de ensino de ciências apontam as potencialidades do engajamento dos estudantes em práticas como argumentação, modelagem e explicação; e que tais práticas estão interligadas ao conhecimento conceitual de ciências. Porém, os modos de promover esta associação e suas implicações ainda não estão claros (Manz, Lehrer & Schauble, 2020).…”
Section: Introductionunclassified
“…Por um lado, pesquisadores têm indicado que explicar como funcionam os processos da ciência, ensinando cada passo da metodologia científica ou desenvolvendo atividades experimentais para que os alunos confirmem o conhecimento conceitual não significa, necessariamente, introduzi-los no legado epistêmico da ciência (Stroupe, 2015;Manz, Lehrer & Schauble, 2020;Ko & Krist, 2019). Seria necessário gerar oportunidades para que estudantes vivenciassem a construção do conhecimento, se apropriando daquilo que estão fazendo a partir de critérios utilizados pela ciência e tomando decisões coletivamente (Carvalho, 2018;Ko & Krist, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…On the one hand, researchers have shown that explanation of how scientific processes work, teaching each step of scientific methodology or developing experimental activities so that the students may confirm conceptual knowledge, does not necessarily mean their introduction into the epistemic legacy of science (Stroupe, 2015;Manz et al, 2020;Ko & Krist, 2019). It would be necessary to create new opportunities so that the students could experience the construction of knowledge, appropriating whatever they are doing based on criteria used by science and collectively taking decisions (Carvalho, 2018;Ko & Krist, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Seeking new options to face such challenges, Duschl (2008) proposes that curricula should be planned based on a balance between the conceptual, epistemic and social learning goals of scientific knowledge. Inquiry-Based Science Teaching is an approach that has the potential to develop a more harmonic curriculum, not centred on concepts alone (Duschl, 2017;Kelly & Licona, 2018;Manz et al, 2020). However, research indicates that are challenges about how to promote this balance through an inquiry-based perspective.…”
Section: Introductionmentioning
confidence: 99%